Serum high-density lipoprotein cholesterol concentration and functional state: The Korean Urban Rural Elderly (KURE) Study. (July 2017) - Choi, Hansol; Kim, Hyeon Chang; Stefani, Katherine M.; Lee, Ju-Mi; Yoon, Young Mi; Lee, Eun Young; Kim, Kyoung Min; Rhee, Yumie; Youm, Yoosik; Kim, Chang Oh
Highlights: A total of 3514 participants aged 65 years or older have been studied. Low HDL cholesterol was defined as a serum HDL cholesterol <40 mg/dL. We assessed functional state with MMSE, ADL, IADL, TUG, and CRT. Higher HDL cholesterol (≥60 mg/dL) was associated with better functional state. HDL cholesterol may be a predictor of impaired functional state among elderly. Abstract: Background: Functional state and cholesterol metabolism are important for older adults; however, this association has not been fully investigated among community-dwelling older adults. Thus, we investigated the association of HDL cholesterol with multiple functional state measures in an elderly Korean population. Methods: This cross-sectional analysis included 3514 participants, aged 65 years or older, who participated in baseline health assessment for the Korean Urban Rural Elderly cohort study from 2012 to 2015. HDL cholesterol concentration was analyzed using both continuous and categorical variables. Functional state was assessed by the mini-mental state examination (MMSE), activities of daily living (ADL) scale, instrumental activities of daily living (IADL) scale, timed up-and go (TUG) test, and chair-rise test (CRT). Multiple logistic regression models were used to investigate independent association between HDL cholesterol and functional state, after adjusting for sex, age, body mass index, systolic blood pressure, fasting glucose, lipid-lowering drug, history of cancer and cardiovascular disease, and health behaviors. Results: HDL cholesterol concentration was significantly associated with MMSE, ADL, IADL, TUG, and CRT in the unadjusted model. After adjustment for covariates, the association remained significant for MMSE (standardized β = 0.059, p = 0.001), ADL (standardized β = −0.053, p = 0.004), and CRT (standardized β = −0.037, p = 0.037). In fully-adjusted model, Participants who had a lower HDL concentration (<40 mg/dL) showed significantly increased odds for having MMSE decline (OR 1.451, 95% CI 1.119–1.883) and ADL dependency (OR 2.251, 95% CI 1.119–4.526), compared reference group (≥60 mg/dL). Conclusions: Higher HDL cholesterol concentration was associated with better functional state among Korean older adults.